2015
DOI: 10.15314/tjse.03754
|View full text |Cite
|
Sign up to set email alerts
|

Examination of flexibility and sprint performance values of adolescent footballers

Abstract: The flexibility is effective to provide an optimal body development appropriate to needs of sports branch and development of physical factors such as strength, speed and sport technique. The purpose of this study is to compare the flexibility and sprint performance values according to age and gender, the features of physical fitness performance of boys and girls who play football. Total of 172 volunteer's measurements were evaluated which consisted of 99 men footballer whose average age are 12,919 0,078 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…There was no significant difference in the elasticity values (p> 0.05). According to Mendes et al the elasticity values of the adolescents were found to be 4,8 ± 0,4 cm (Mendes et al, 2015). Rye recorded the elasticity values of girls aged 12-14 years as 19.66 ± 4.35 cm, 22.38 ± 5.29 cm (Çavdar, 2006).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There was no significant difference in the elasticity values (p> 0.05). According to Mendes et al the elasticity values of the adolescents were found to be 4,8 ± 0,4 cm (Mendes et al, 2015). Rye recorded the elasticity values of girls aged 12-14 years as 19.66 ± 4.35 cm, 22.38 ± 5.29 cm (Çavdar, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Thomas and his colleagues found that the footballers average speed of 10 m and 20 m were 1.69 ± 00.1 s and 3.10 ± 00.1 s, respectively (Thomas et al, 2012). Mendes and al. found that the sprint grades of 10 m and 20 m were 2.02 ± 0.01 s and 3.82 ± 0.03 s, respectively, in adolescent soccer players (Mendes et al, 2015). AugheyWyckels et al found that 20 m sprint averages were 3.47 ± 0.13 sec.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Por otro lado, en el contexto de un diseño experimental llevado a cabo con nueve jugadoras juveniles de fútbol, Mathisen & Pettersen (2015) también valoraron el tiempo empleado en los primeros 10 metros de un test de sprint de 20 m, y encontraron valores medios de base de 1,99 s y 1,95 s en dos grupos con edades de 15,5 ± 0,7 años y 15,1 ± 0,5 años (media ± desviación estándar). Y Mendes et al (2015) aplicaron el test de sprint de 10 m a 99 varones y 72 mujeres jugadores de fútbol con rangos de edad de 11,0 a 14,0 años y 12,0 a 14,0 años, respectivamente. Ellos encontraron un tiempo medio de 1,86 s en varones, y 2,02 s en mujeres.…”
Section: Discussionunclassified